Listening Comprehension Problems with English lectures - قصي محمد دهام (College of Education for Women, 2019)
The purpose of this study is to investigate learners' listening comprehension problems with Englishlectures. The study was guided by research question (What are the listening comprehension problems learners have with lectures in English).Furthermore; the main significant goal were declared through conducting this study, as well as providing some procedures of distribution the questionnaire of the study.Moreover, it presents several definitions of listening. This study definitely depends on questionnaire instrument to gathering the required data. The participants of the study were 30 learners completed their secondary school and joined at the college. Based on the findings among the five factors (text, speaker, task, environment, and listener) that affecting listening comprehension. The study showed that the most frequently factors among the respondents is the task factor followed by speaker factor then the listener factors and the least two factors were the text and environment factors. Results also showed that learners' encountered problems related to learners accent and speech rate new vocabulary items and unfamiliar topics.